THE EFFECT OF EXPERIENCE AND GREEN MARKETING ON MS GLOW MEN’S CUSTOMER LOYALTY - Raihan Wishal Nafis; Muhammad Syarif Hidayatullah Elmas; Agustina Pujiastuti (SEGMEN: Jurnal Manajemen dan Bisnis, 2023)
This study aims to analyze whether or not the effect of experience and green marketing on customer loyalty. The sample of this research is 240 users of MS Glow Men product using a questionnaire distributed using purposive sampling technique. This research uses multiple linear regression method. The results of the analysis show that green marketing has a positive and significant effect on customer loyalty, where the significance value of the t-test is 0.020 (<0.05) and the regression coefficient is positive at 0.188. Experience has a positive and significant effect on customer loyalty, where the significance value of the t-test is 0.005 (<0.05) and the regression coefficient has a positive value of 0.255. Experience and green marketing together have a positive and significant effect on customer loyalty, it is acceptable.Keywords: Experience, Green Marketing, Customer Loyalty